ANALISIS PENERIMAAN PAJAK HOTEL PADA KANTOR BADAN PENGELOLA PAJAK DAN RETRIBUSI DAERAH KOTA MANADO - Lestari, Indah Diah; Manossoh, Hendrik; Afandy, Dhullo (Universitas Sam Ratulangi, 2018)
Hotel tax is a local tax imposed under the law number 28 of 2009 on local taxes and user charges. The guidelines for the management of regional finances and procedures for the implementation of regional revenue managed by the treasurer of revenue has been regulated in the Minister of Home Affairs Regulation number 59 at 2007 article 89. The purpose of this study to analyze the adequacy of the Tax Admission System and Procedure At the Office of Manado Regional Tax and Retribution Agency. The method used is descriptive analysis. Data were obtained through field studies. The result of this research is the Implementation of Hotel Tax Admission System and Procedure at the Office of Regional Tax and Retribution Manado City has been suitable with the applicable regulations from the Minister of Home Affairs Regulation number 59 at 2007 includes the related functions and documents used as well as the division of tasks and responsibilities. So it is expected that in the next year the Manado Regional Tax and Retribution Board may renew the Regulation of the Minister of Home Affairs or the applicable local government regulation concerning the System and Procedure of Revenue of Original Revenue, especially for the Hotel Tax to be better and effective.Keywords: Hotel Tax Reception, Local Tax, Tax Admission System